Antimicrobial activity of dietary supplements based on bacterial lysate of Lactobacillus rhamnosus DV - Penchuk, Yurii; Savytska, Maryana; Kobyliak, Nazarii; Ostapchenko, Danylo; Kolodiy, Igor; Onysenko, Svitlana; Tsyryuk, Olena; Korotkyi, Oleksandr; Grygoriev, Fedir; Falalyeyeva, Tetyana (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction: According to WHO, antibiotic resistance is increasing to hazardous levels worldwide. Candidiasis often occurs after taking antibiotics. Therefore, antibiotic resistance is a global problem and searching for antibacterial agents is necessary. Aim: to determine the antimicrobial activity of bacterial lysate of Lactobacillus (L.) rhamnosus DV separately and with plant extracts against bacterial and yeast test cultures. Material and methods: Antimicrobial activity of Del-Immune V® (cell wall and DNA fragments from a L. rhamnosus DV) separately and with cinnamon, beetroot, black currant extracts was determined by the minimum inhibitory concentration (MIC). Two-fold serial dilutions determined the MIC in previously prepared meat-peptone broth (MPB) for bacteria and liquid wort for yeast. Gram-negative (Escherichia coli IEM-1, Proteus vulgaris PА-12, Pseudomonas sp. MI-2, L. rhamnosus 13/2) and gram-positive (Bacillus (B.) subtilis BТ-2, Staphylococcus aureus BМС-1) bacteria, as well as yeast (Candida (C.) albicans D-6, C. tropicalis PE-2, C. utilis BVS-65) were used as test cultures. Results: MIC for the studied bacterial test cultures after application of L. rhamnosus DV bacterial lysates was from 1.0±0.05 to 12.5±0.63 mg/mL, which was significantly less than the thermally inactivated control (MIC from 125.0±6.25 to 250.0±12.5 mg/mL). B. subtilis BT-2 culture was the least sensitive to the action of the bacterial lysate (MIC – 12.5±0.63 mg/mL). It showed the best antibacterial and anti-fungal effects bacterial lysate with the phytonutrient Black currant. Conclusions: It was demonstrated that bacterial lysate of lactic acid bacteria L. rhamnosus DV exhibits antibacterial and anti-fungal properties during direct contact with pathogenic agents.